2017
DOI: 10.1371/journal.pone.0177643
|View full text |Cite
|
Sign up to set email alerts
|

Environmental DNA (eDNA) metabarcoding assays to detect invasive invertebrate species in the Great Lakes

Abstract: Describing and monitoring biodiversity comprise integral parts of ecosystem management. Recent research coupling metabarcoding and environmental DNA (eDNA) demonstrate that these methods can serve as important tools for surveying biodiversity, while significantly decreasing the time, expense and resources spent on traditional survey methods. The literature emphasizes the importance of genetic marker development, as the markers dictate the applicability, sensitivity and resolution ability of an eDNA assay. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
171
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(181 citation statements)
references
References 52 publications
9
171
1
Order By: Relevance
“…However, not all water quality indices are based on families, and the taxonomic level demanded for monitoring programs varies significantly among countries (Bonada et al, 2005). Although some studies have tried to relate the sequence reads with individual abundance metrics (Klymus, Marshall, & Stepien, 2017;Ushio et al, 2018), it is still not possible to do it with the metabarcoding analysis carried out in this study. On the other hand, quantitative elements are also currently required within the WFD.…”
Section: Discussionmentioning
confidence: 97%
“…However, not all water quality indices are based on families, and the taxonomic level demanded for monitoring programs varies significantly among countries (Bonada et al, 2005). Although some studies have tried to relate the sequence reads with individual abundance metrics (Klymus, Marshall, & Stepien, 2017;Ushio et al, 2018), it is still not possible to do it with the metabarcoding analysis carried out in this study. On the other hand, quantitative elements are also currently required within the WFD.…”
Section: Discussionmentioning
confidence: 97%
“…The spacer region increased nt diversity of sequence reads and enhanced cluster formation, improving sequencing quality (Fadrosh et al, ; Wu et al, ). Four primer sets were used, which differed in their spacer combinations (see Klymus et al, ). PCR conditions were identical, except that the cycle number was reduced to eight.…”
Section: Methodsmentioning
confidence: 99%
“…Conditions were as follows: 30‐s initial denaturation at 95°C, followed by eight cycles at 95°C for 30‐s, 55°C for 30‐s, and 68°C for 1‐min, with a final 2‐min 68°C extension. Four samples were run with the Mol16S primer set followed the library preparation, which was published in Klymus et al ().…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental DNA metabarcoding has been widely used for environmental assessment, such as detection of invasive species (e.g., Klymus, Marshall, & Stepien, ), water quality assessment in rivers and streams (e.g., Apothéloz‐Perret‐Gentil et al., ; Zimmermann, Glöckner, Jahn, Enke, & Gemeinholzer, ), impacts of oil drilling (e.g., Lanzén, Lekang, Jonassen, Thompson, & Troedsson, ) as well as benthic impacts of marine finfish farms (e.g., Pawlowski, Esling, Lejzerowicz, Cedhagen, & Wilding, ). Several eDNA metabarcoding studies on benthic impacts of salmon farming found results obtained using eDNA metabarcoding were comparable to those obtained using complex biological indices that require macrofaunal inventories characterized by traditional morpho‐taxonomy (Dowle, Pochon, Keeley, & Wood, ; Lejzerowicz et al., ; Pawlowski et al., , ; Pochon et al., ; Stoeck, Frühe et al., ).…”
Section: Introductionmentioning
confidence: 99%